Cardiology in family practice : a practical guide - Hollenberg, Steven M.; Heitner, Stephen (Current clinical practice series, 2012)
The second edition ofCardiology In Family Practice: A Practical Guide offers a clear description of state-of-the-art approaches to cardiovascular illnesses specifically tailored for family physicians and primary care practitioners.¡ Comprehensively updated from the first edition in 2006, this revision includes discussion of: ¡ -stable angina -acute coronary syndromes -arrhythmias -hypertension -congestive heart failure -valvular disease -pericardial diseases -prevention of bacterial endocarditis -hyperlipidemia ¡ Containing illustrations and ECGs and written in an easy-to-read format and emphasizing practical techniques for evaluation and treatment, Cardiology in Family Practice, second edition, remains a concise and useful summary of the most important medical and scientific cardiovascular topics for the primary care environment.